Pengaruh pemberian edukasi pengetahuan operasi dengan kecemasan preoperasi pasien pada tindakan spinal anestesi - Prasetia, Muhamad Agung; Sunarsih, Sunarsih; Puri, Anita; Murhan, Al (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2023)
Background: Surgery and anesthesia are actions that bring stress, because there is a threat to the integrity of one's body and soul. The existence of this stress can cause anxiety conditions for patients. Several studies that have been done say that about 60% -80% of patients who will undergo surgery will experience preoperative and pre-anesthesia anxiety in various levels. Data obtained from the World Health Organization (WHO) shows that the number of patients undergoing surgery has increased significantly from year to year. It was recorded that in 2011 there were 140 million patients in all hospitals in the world, while in 2012 the data increased by 148 million people. Data from the National Tabulation of the Ministry of Health of the Republic of Indonesia in 2016, explains that surgery ranks 11th out of 50 disease patterns in Indonesia with a percentage of 12.8% and it is estimated that 32% of them are major surgery, and 25.1% have mental conditions and 7% experiencing anxiety. Purpose: To find out how the effect of providing surgical knowledge education on preoperative anxiety of patients with spinal anesthesia at Regional General Hospital Dr. H. Abdul Moeloek Lampung Province in 2022. Method: This type of research is quantitative with Quasy Experiment design with Non Equivalent Control Group Design. The sampling technique used is a probability sampling technique, namely purposive sampling. The population in this study were all patients who underwent surgery under spinal anesthesia at Regional General Hospital  Dr. H. Abdul Moeloek. Collecting data using a questionnaire sheet using the Independent T-test. Results: The results of the study were obtained by using a parametric test using an Independent T-test and p-value = (0.000) < (0.05). Conclusion: Researchers hope that knowledge education can be given to preoperative patients not only with spinal anesthesia but for all patients who will undergo surgery to help overcome anxiety.   Keywords: Spinal Anesthesia; Operation Knowledge Education; Preoperative Anxiety.   Pendahuluan: Tindakan pembedahan dan anestesi merupakan tindakan yang mendatangkan stress, karena terdapat ancaman terhadap integritas tubuh dan jiwa seseorang. Adanya stress tersebut dapat menimbulkan suatu kondisi kecemasan terhadap pasien. Beberapa studi yang pernah dilakukan menyatakan bahwa sekitar 60%-80% pasien yang akan menjalani operasi akan mengalami kecemasan pre operasi dan pre anestesi dalam berbagai tingkatan. Data yang diperoleh dari World Health Organization (WHO) jumlah pasien dengan tindakan operasi mencapai angka peningkatan yang sangat signifikan dari tahun ke tahun. Tercatat ditahun 2011 terdapat 140 juta pasien di seluruh rumah sakit di dunia, sedangkan pada tahun 2012 data mengalami peningkatan sebesar 148 juta jiwa. Data Tabulasi Nasional Departemen Kesehatan RI Tahun 2016, menjabarkan bahwa tindakan bedah menempati urutan ke-11 dari 50 pola penyakit di Indonesia dengan persentase 12,8% dan diperkirakan 32% diantaranya merupakan bedah mayor, dan 25,1% mengalami kondisi kejiwaan serta 7% mengalami kecemasan. Tujuan: Untuk mengetahui bagaimana pengaruh pemberian edukasi pengetahuan operasi terhadap kecemasan preoperasi pasien dengan tindakan spinal anestesi di RSUD Dr. H. Abdul Moeloek Provinsi Lampung tahun 2022. Metode: Jenis penelitian ini kuantitatif dengan rancangan Quasy Eksperimen dengan rancangan Non Equivalent Control Grup Design. Teknik pengambilan sampel menggunakan teknik probiliy sampling yaitu dengan purposive sampling.Populasi dalam penelitian ini adalah seluruh pasien menjalani tindakan operasi dengan anestesi spinal di RSUD Dr. H. Abdul Moeloek. Pengumpulan data menggunakan lembar kuisioner dengan menggunakan uji T-Independent. Hasil: Penelitian di dapatkan uji parametik dengan menggunakan uji T-Independent dan didapatkan nilai p-value = (0.000) < α (0.05). Simpulan: Peneliti berharap edukasi pengetahuan dapat diberikan pada pasien preoperasi bukan hanya dengan anestesi spinal tetapi untuk semua pasien yang akan menjalani tindakan operasi untuk membantu mengatasi kecemasan.